Physical rehabilitation in pediatrics. The educational manual - Mikhalyuk, E. L.; Tkalich, I. V.; Cherepok, A. A.; Михалюк, Євген Леонідович; Ткаліч, Ігор Вячеславович; Черепок, Олександр Олексійович (Zaporozhye state medical university, 2016)
Study book is intended for independent work of students of medical faculties IV course in preparation for the practical training in the discipline "Physical rehabilitation and sports medicine"